Barriers and facilitators in developing patient versions of clinical practice guidelines - qualitative interviews on experiences of international guideline producers - Nora Meyer; Julia Hauprich; Jessica Breuing; Irma Hellbrecht; Sarah Wahlen; Nadja Könsgen; Stefanie Bühn; Monika Becker; Susanne Blödt; Günther Carl; Markus Follmann; Stefanie Frenz; et al. (BMC, 2024)
Abstract Background Several guideline organizations produce patient versions of clinical practice guidelines (PVGs) which translate recommendations into simple language. A former study of our working group revealed that few guideline organizations publish their methods used to develop PVGs. Clear definitions of PVGs do not prevail and their purposes often remain unclear. We aimed to explore experts' perspectives on developing, disseminating and implementing PVGs to discuss and incorporate these experiences when consenting on methodological guidance and further improving PVGs. Methods We conducted 17 semi-structured telephone interviews with international experts working with PVGs from September 2021 through January 2022. We conducted the interviews in English or German, they were recorded and transcribed verbatim. We utilized Mayring's qualitative content analysis with MAXQDA software to analyze the data. Results In two interviews two participants were interviewed at the same time. This resulted in a total of 19 participants from 16 different organizations and eight different countries participated. Most were female (16/19) and their experience in working with PVGs ranged from 1 to 20 years. All follow methodological standards when developing PVGs, but the extent of these standards and their public accessibility differs. Aims and target groups of PVGs vary between organizations. Facilitators for developing PVGs are working with a multidisciplinary team, financial resources, consultation processes and a high-quality underlying CPG. Facilitators for disseminating and implementing PVGs are using various strategies. Barriers, on the other hand, are the lack of these factors. All participants mentioned patient involvement as a key aspect in PVG development. Conclusion The steps in the PVG development process are largely similar across the countries. Focus is placed on the involvement of patients in the development process, although the extent of participation varies. The experts collectively attribute great importance to PVGs overall, but in order to constantly adapt to medical progress and changing conditions, the focus in the future may be more on formats like living guidelines. Although there are different views on the mandatory development of PVGs, there is a consistent call for more transparency regarding the methodology used for PVGs.